Mass-forming extramedullary hematopoiesis mimicking Hodgkin's lymphoma - BOZKURT, SÜHEYLA (MARMARA UNIV, FAC MEDICINE, 2019)
Extramedullary hematopoiesis (EMH) refers to the proliferation of hematopoietic precursors outside the bone marrow. EMH often presents as a mass lesion in several areas of the body. In this report, we present a case misdiagnosed and explain the cause of the diagnostic error.
Keywords: Extramedullary hematopoiesis; Posterior mediastinal mass; Hemolytic anemia; NEOPLASMS